Monitoring of iron, lipid and liver profiles in Egyptian hepatitis C virus patients on sofosbuvir therapy - Hussein A. AbdEl-maksoud; Mohamed G. Elharrif; Omnia Abd El-hamid; Saad M. Alsaab; Eman M. El-sorady (Elsevier, 2022)
Hepatitis C virus is a major cause of inflammation of liver tissue. In serious cases the disease can progressed to cirrhosis, fibrosis, hepatocellular carcinoma and end stage liver disease. The research was designed to monitoring the iron, lipid and liver profiles in hepatitis C patients before and during treatment with sofosbuvir antiviral drug. To achieve this aim, the study was conducted on 22 patients with hepatitis C virus infection and 9 control normal volunteers after taking their consent. The monitoring done through biochemical determination of serum iron, ferritin, transferrin as well as total iron binding capacity. Also, serum cholesterol, triglycerides, HDL, LDL, VLDL, AST, ALP, total protein and albumin was determined. The result showed that, the increased serum iron (205.59±8.27 μg/dl), cholesterol (237.96 ± 10.92 mg/dl), triglycerides (246.58 ± 8.23 mg/dl), LDL (172.82 ± 8.47 mg/dl), VLDL (50.91 ± 1.65 mg/dl), AST (164.58 ± 8.45 U/L), ALP (142.61 ± 7.41 U/L) in hepatitis C virus patients was significantly decreased (P < 0.05) upon treatment with sofosbuvir and the decreased serum ferritin (18.55±1.39 ng/dl), transferrin (128.41 ± 6.43 mg/dl), total iron binding capacity (204.41 ± 8.82 mg/dl), total protein (5.81 ± 0.24 g/dl), albumin (2.83 ± 0.09 g/dl) and HDL (14.22 ± 1.17 mg/dl) in hepatitis C virus patients was significantly increased (P < 0.05) upon treatment with sofosbuvir. According to our finding we concluded that, treatment with sofosbuvir 12 week ameliorate disruption of iron, lipid and liver parameters caused by infection with Hepatitis C virus.